2005
DOI: 10.1007/s11045-005-6862-9
|View full text |Cite
|
Sign up to set email alerts
|

Control and Disturbance Rejection for Discrete Linear Repetitive Processes

Abstract: Repetitive processes are a distinct class of 2D systems (i.e. information propagation in two independent directions) of both systems theoretic and applications interest. They cannot be controlled by direct extension of existing techniques from either standard (termed 1D here) or 2D systems theory. Here we give new results on the relatively open problem of the design of physically based feedforward/feedback control laws to achieve desired performance and disturbance decoupling in the sense defined in the body o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Lemma 2. Given a scalar 2 > 0, the augmented system (42) is stochastically stable with an H ∞ disturbance attenuation level 2 Proof. Similar to the proof of Lemma 1, we introduce a stochastic Lyapunov function for augmented system (42) as…”
Section: Controller Design Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lemma 2. Given a scalar 2 > 0, the augmented system (42) is stochastically stable with an H ∞ disturbance attenuation level 2 Proof. Similar to the proof of Lemma 1, we introduce a stochastic Lyapunov function for augmented system (42) as…”
Section: Controller Design Conditionmentioning
confidence: 99%
“…Theorem 2. Given a scalar 2 > 0, the augmented system (42) is stochastically stable with an H ∞ disturbance attenuation level 2…”
Section: Controller Design Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof The inequalities (16) and (18) are equivalent to r( A) < 1 and r( D 0 ) < 1, respectively (Sulikowski, Galkowski, Rogers, & Owens, 2005). Now consider the controlled process version of (8), i.e.…”
Section: Theorem 3 Suppose That a Control Law Of The Form (9) Is Applmentioning
confidence: 99%
“…This represented a full survey on linear and nonlinear ILC. Disturbance rejection and control is seen in (Sulikowski et al, 2005) where convergence conditions of adaptive ILC is reported in Owens and Munde (2000). Exponential stability is investigated in Dymkov et al (2002) where French et al (2001) proposed a two-dimensional (2D)-approach discrete time ILC technique.…”
Section: Introductionmentioning
confidence: 99%